2020
DOI: 10.1038/s41598-020-58276-0
|View full text |Cite
|
Sign up to set email alerts
|

Not all cicadas increase thermal tolerance in response to a temperature gradient in metropolitan Seoul

Abstract: Rapid anthropogenic alterations caused by urbanization are increasing temperatures in urban cores, a phenomenon known as the urban heat island (UHI) effect. Two cicada species, Cryptotympana atrata and Hyalessa fuscata (Hemiptera: cicadidae), are abundant in metropolitan Seoul where their population densities correlate strongly with UHI intensities. Such a positive correlation between cicada density and UHI intensity may be possible if cicada abundance is linked to a certain thermal tolerance. We tested this h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…As a result, those individuals who cannot cope with thermal stress may experience irreversible cell death, or at least lower fertility. In contrast, the positive association between the localized thermal regime and thermal responses of cicadas inhabiting warm areas in metropolitan Seoul showed that those individuals could increase their heat endurance as the temperature conditions of their habitat increased [45]. Furthermore, bigger body sizes, which is an indicator of higher reproducibility, were also observed in females living in warm areas, which indicated a possible close relationship between female fecundity and thermal tolerance.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…As a result, those individuals who cannot cope with thermal stress may experience irreversible cell death, or at least lower fertility. In contrast, the positive association between the localized thermal regime and thermal responses of cicadas inhabiting warm areas in metropolitan Seoul showed that those individuals could increase their heat endurance as the temperature conditions of their habitat increased [45]. Furthermore, bigger body sizes, which is an indicator of higher reproducibility, were also observed in females living in warm areas, which indicated a possible close relationship between female fecundity and thermal tolerance.…”
Section: Discussionmentioning
confidence: 86%
“…This was attributed to the urban heat island (UHI) effect, which is a phenomenon that occurs when urban cores become hotter than the surroundings [44]. A positive relationship between the thermal responses of cicadas and the intensity of the urban heat island effect was documented [45]. This finding suggests the potential adaptation of this cicada species to warm urban cores in Seoul.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Such studies include on termites and other tree-boring insects that produce feeding sounds that have spectral and temporal patterns like those of stored product insects [ 94 , 95 , 142 , 143 , 235 ]. Others describe effects of temperature on rates of activity [ 60 ]. Others incorporate optical sensors in traps [ 150 , 275 ] with similarities to pitfall traps used for monitoring stored product insects [ 236 ].…”
Section: Discussionmentioning
confidence: 99%